FIQH MUAMALAH REVIEW OF AUCTION SALE AND PURCHASE OF COLLATERAL AT KANTOR KEKAYAAN NEGARA DAN LELANG (KPKNL) SIDOARJO - Muhammad Akbar Maulana; Achmad Yasin (Lafadz Jaya Publisher, 2023)
Auction is one of the buying and selling that has been implemented for a long time. This study aims to find out how the auction process took place, especially at the Sidoarjo KPKNL and Islamic views regarding auction implementation. Basically, an auction is a type of sale and purchase so that the legal terms and pillars of the auction have the same thing. Many scholars argue about auctions, with all the risks that occur. Research uses qualitative methods with data collection techniques using interview techniques, documentation and in-depth observation which are managed and studied by researchers. The auction at the Sidoarjo KPKNL has fulfilled the requirements and is legal in Islam, and complies with binding laws regarding the implementation of the auction. The Sidoarjo KPKNL also issued innovations so that auctions that occur can provide a sense of security and comfort to users of auction services.